Modelling dynamics of victims' stress during natural disaster - Ali, Hayder Mohammed Ali (2014)
Natural disaster is one of the inescapable phenomenon through which numerous number of individuals are being affected via developing psychological problems. Stress is one of the essential psychological effects of natural disaster; it is a reality of nature where forces from the outside world affect individuals exposed to such phenomenon. In computational psychology domains, computational models were used as tools for understanding human cognitive functions and behavioural patterns. Meanwhile, psychological and cognitive theories as well as empirical studies have provided convergent evidence to identify important factors and psychological attributes that affect the stress level of victims during natural disaster. Therefore, this study implements a formal model (computational model) to understand the current state of victims' stress during natural disaster. From related theories, 22 of basic factors have been established and grouped into 7 main categories that include predisposed factors, resources, individual attributes, appraisal, resilience, coping, and stress. Those factors provide the fundamental knowledge of the behaviours of victims after disaster occurrence. A formal model was developed by using a set of differential equations. Later, this model was simulated by applying related scenarios based on three different cases, namely; 1) a good victim with low level of stress, 2) victim with high level of stress, and 3) victim with moderate level of stress) through the use of Matlab as a programming language. This computational model was then verified using two techniques; 1) logical verification (Temporal Trace Language) and 2) mathematical verification (stability analysis). The experimental results have approximately predicted why victims develop stress differently when facing natural disasters.